ANALISIS SISTEM DAN PROSEDUR PENGHAPUSAN BARANG MILIK NEGARA PADA KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI SULAWESI UTARA - Kiay Demak, Indah Namira; Manossoh, Hendrik; Afandi, Dhullo (Universitas Sam Ratulangi, 2018)
State goods are all goods purchased or obtained at the expense of the State Revenue and Expenditure Budget or derived from other legitimate acquisitions. Elimination of state property is the final activity of the implementation of the management of state property and is an act that is not simple for government agencies. The publication of decisions on the abolition of state property occurs through procedures that are often seen as complicated and time consuming. This study aims to determine whether the system and procedures for the elimination of State Property at the Regional Office of the Ministry of Religious Affairs of North Sulawesi Province has been in accordance with Regulation of the Minister of Finance No. 83 / PMK.06 / 2016 on the Procedures for the Implementation of Destruction and Elimination of State Property, as seen from or not fulfillment of elements of internal control system of government according to Government Regulation Number 60 Year 2008 regarding Government Internal Control System. The research method used in this thesis research is descriptive method whose purpose each data collected, analyzed, then drawn a conclusion and the type of research used is qualitative descriptive. The results of this study concluded that the system and procedures for the elimination of state property in the Regional Office of the Ministry of Religious Affairs of North Sulawesi Province have been in accordance with the Regulation of the Minister of Finance No. 83 / PMK.06 / 2016 on the Procedures for Implementation of Destruction and Elimination of State Property, and has fulfilled the elements of the internal control system of government according to Government Regulation Number 60 Year 2008 regarding Government Internal Control System.Keywords: Analysis, Systems and Procedures, Elimination of State Property.